Computed Tomography Angiography in Peripheral Arterial Disease: Comparison of Three Image Acquisition Techniques to Optimize Vascular Enhancement—Randomized Controlled Trial - Rotzinger, David C.; Lu, Tri-Linh; Kawkabani, Aida; Marques-Vidal, Pedro-Manuel; Fetz, Gianluca; Qanadli, Salah D. (Frontiers in Cardiovascular Medicine, 2020)
Objectives To prospectively compare three image acquisition techniques in lower extremity CT angiography: the “standard” anterograde technique (SA), the adaptive anterograde technique (AA), and the retrograde acquisition technique (RA). Materials and Methods Sixty consecutive patients were prospectively enrolled and randomized into three acquisition groups: 20 patients were evaluated with SA, 20 with AA as described by Qanadli et al., and 20 with caudocranial acquisition from the feet to the abdominal aorta (RA). Quantitative image quality was assessed by measuring the intraluminal attenuation at different levels of interest, with a total of 536 levels. Qualitative image quality was assessed by two radiologists in consensus using a Likert scale to rate the arterial enhancement and venous return. For each patient and limb, the presence of occlusive or aneurysmal disease was documented. Results In quantitative analysis, RA showed lower attenuation values than to SA and AA (p < 0.01). AA showed the highest and most homogeneous attenuation along the arterial tree. In qualitative analysis, AA had the lowest rate of non-diagnostic vascular segments (3.9%) compared to SA and RA (4.7 and 13.1%, respectively, p < 0.01). The influence of venous return was significantly different among the different techniques; venous contamination was particularly prevalent at the aortic level with RA (9.4% of patients, 0% with SA and AA, p < 0.01). The presence of stenosis or occlusion had no significant influence on the attenuation values across all levels and acquisition techniques. Conversely, the presence of aneurysmal disease had a significant effect on the luminal attenuation in AA (higher attenuation) and RA (lower attenuation) at the iliac (p = 0.03 and 0.04, respectively) and femoral levels (p = 0.02 and <0.01, respectively). Conclusion Considering both quantitative and qualitative analysis, AA performed better than SA and RA, providing the highest percentage of optimal vascular enhancement. AA should be recommended as the technique of choice, specifically in the presence of aneurysmal disease. Alternatively, SA can be useful in case of renal failure, as the test bolus is unnecessary. Finally, the increasing availability of fast CT systems will likely overcome the limitations of RA.